PENERAPAN PENDEKATAN MASTERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN JASMANI OLAH RAGA DAN KESEHATAN DENGAN MATERI LOMPAT JAUH GAYA JONGKOK (SISWA KELAS VIII SMP NEGERI 1 KREMBUNG SIDOARJO) - INDRAYANTO, ARI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Based on the observation result on SMP Negeri 1 Krembung,  Sub district Krembung  District Sidoarjo especially on class VIII G, show that on learning process still teacher oriented. Beside, student only execute practice activity with pickup equipment, without the help of learning instrument that applied in conveying learning matter. Also, if student get score under the minimum completeness standard criterion, teacher give no help to student in involved to improve it. It cause the lack of maximal on learning result that obtained by student. So in this research, researcher choose one of the learning approach that give special action based on student need. The aim that achieved are to knowing the effectiveness of the application of mastery learning seen from student activity, teacher ability in teaching and learning result that obtained by student on learning and student respond during learning take place. This learning use data analysis technique with qualitative and quantitative approach to obtain data through observation, test, questioner, and interview method. Data obtained will analyzed and present descriptive quantitatively and qualitatively. Research execute in three cycles. Research result show that by applying mastery learning can increase student-learning result  with score average that obtained on first cycle as big as 63.88%, second cycle 72.22% and third cycle as big as 86.11%. beside, from the research result also show that there is improvement of student activity, teacher activity on learning and student respond during learning. It can be conclude that long jump squat style matter  can be teach by applying mastery learning because can increasing student learning result during learning. Keywords: mastery learning approach, learning result, physical education sport and healt